A large malignant oncocytoma of parotid gland: a case report - Sreedevi, Nidhi Mohan; Vernekar, Sunita S.; Samee, Mohammed M. Abdus; Dandinarasaiah, Manjunath (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Malignant oncocytoma is an extremely rare neoplasm of the salivary gland accounting for 0.5% of epithelial salivary gland malignancies and 0.18% of epithelial salivary gland tumors. We report a case of malignant oncocytoma of left parotid gland in a 61-year old female patient. Patient presented with a 6-year history of painless swelling in the left parotid region. Fine needle aspiration cytology of the swelling was suggestive of pleomorphic adenoma. A computed tomography scan performed did not reveal any features suggestive of malignancy. Patient underwent left superficial parotidectomy. However, histopathological examination of the specimen turned out to be malignant oncocytoma. Malignant oncocytoma of salivary glands have rare incidence and may have similar morphologic features with other neoplasms. Despite the tumor being large and malignant in this case, there was no facial palsy preoperatively. As histopathology is often diagnostic, the possibility of malignancy always must be kept in mind preoperatively even when there is no facial palsy or fine needle aspiration cytology not showing up malignancy.